EVALUATION OF THE COACHING TEAMS PROJECT TO ENHANCE THE QUALITY OF EDUCATION - Wangkum, Tavin; Thepsorn, Kanchana; Puengsuk, Krongthip (PUPIL: International Journal of Teaching, Education and Learning, 2020)
The purpose of this research was to the assessment of the “Coaching Teams” for increasing evaluation quality. The assessment model of the AMET project developed consists of 4 assessment points, which are appropriate assessment, monitoring assessment, efficiency assessment, and transfer of knowledge assessment. Find content validity by experts assess the consistency between each assessment and the objectives to be evaluated. The expert’s evaluation found that the consistency index is between 0.60-1.00. When evaluating the Coaching Teams project to improve the quality of education, the budget year 2019 of 11 schools, it is found that the appropriate assessment, monitoring assessment, efficiency assessment, and transfer of knowledge assessment were accordance with the objectives of the project. The average consistency of the evaluation results is 4.60–4.80 and the standard deviation is 0.45–0.55.